Top of mind: as lojas de vestuários local mais lembradas pelos discentes do curso de Administração da UFAM – campus Parintins - Carvalho, David Pereira de (Brasil, 2025)
This research aims to conduct a survey on the concept of Top of Mind as a branding strategy, investigating which clothing brands come immediately to the minds of students from the Administration course at the Federal University of Amazonas (UFAM - Parintins campus). The study seeks to identify the brands that are immediately remembered by these students, exploring aspects such as memory, consumer behavior, socioeconomic profile, and brand recall. The main objective is to identify which clothing stores occupy the top positions in the top of mind of UFAM Administration students in the first semester of 2024. To this end, descriptive research was conducted based on the application of structured questionnaires and the use of a quantitative approach. The survey included the identification of enrolled students, the analysis of the most remembered clothing stores, the socioeconomic profile of the participants and the composition of the podium of the most mentioned brands. The results showed that the three most remembered stores were Ideal Tecidos, Lojão Caruaru and Parintins Beach, standing out as the brands that occupy the students' first thoughts. Based on these findings, it is recommended that the most mentioned brands consolidate their strategies to maintain their leadership, while the least remembered ones should strengthen their presence through more effective marketing actions, aiming to achieve greater prominence in future rankings. The relevance of this study lies in its contributions to future research, serving as a basis for explanatory and exploratory investigations. In addition, it offers valuable foundations for more assertive consulting and business decisions, providing insights that help companies develop more impactful marketing strategies. Finally, it highlights the importance of organizations improving their visual identity and reinforcing their presence in the consumer's memory through branding.